Women and Fairness Navigating an Unfair World - Lambertsson Björk, Eva; Eschenbach, Jutta; Wagner, Johanna M. (Waxmann Verlag, 2021)
This collection brings together scholars from various disciplines to ask fundamental questions concerning how women handle the manifold impediments placed before them as they simply attempt to live full human lives. The collection explores narratives of women - real and fictional - who fight against these barriers, who succumb to them, who remain unaware of them, or choose to ignore them. It explores the ways we read women in cultural production, and how women are read in society. We assert the obstacles constructed into the very fabric of societies against fifty percent of the population are unfair, be they hindrances for women to attain their goals, encumbrances that limit women's speech and societal participation - communal and artistic - or hindrances that prohibit specific behaviors and images of women.